2014
DOI: 10.1080/00131911.2014.927829
|View full text |Cite
|
Sign up to set email alerts
|

The implications of school improvement and school effectiveness research for primary school principals in Ethiopia

Abstract: In the last twenty years the Ethiopian education system has rapidly expanded, leading to a 500% increase in primary school enrolment. The Ministry of Education (MoE) has sought to address a perceived decline in educational quality through nationally-mandated programmes for school improvement (MoE 2007) and teachers ' professional development (MoE 2004). Such programmes-imported on the advice of USAID, DfID and other development partners-are implemented 'mechanistically', without adaptation for societal or org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…As other researchers have highlighted, the relationship between the woreda education office and school principals is key in strengthening school-based capacity (e.g. Yadete, 2012;Mitchell, 2015), and we found that this is particularly true in the context of responding to the COVID-19 pandemic. The support that school principals receive from the local government had knock-on effects for how they respond and interact with teachers, parents and caregivers, as well as woreda education officials.…”
Section: Support Is Critical In Strengthening Local-level Capacitysupporting
confidence: 60%
See 2 more Smart Citations
“…As other researchers have highlighted, the relationship between the woreda education office and school principals is key in strengthening school-based capacity (e.g. Yadete, 2012;Mitchell, 2015), and we found that this is particularly true in the context of responding to the COVID-19 pandemic. The support that school principals receive from the local government had knock-on effects for how they respond and interact with teachers, parents and caregivers, as well as woreda education officials.…”
Section: Support Is Critical In Strengthening Local-level Capacitysupporting
confidence: 60%
“…First, the centralised nature of education planning is suggested to be at odds with efforts to decentralise the education system and building local-level capacity (Iyer & Rossiter, 2018). This often results in limited ownership and significant knowledge gaps at lower levels of the education system, which are in turn exacerbated by an over-reliance on inefficient modes of information communication and dissemination (Asegdom et al, 2019;Gibbs et al, 2020;Mitchell, 2015;Yadete, 2012). Secondly, the top-down nature of the system and upward nature of accountability upon which the education system is predicated leads to a lack of flexibility in adapting nationally/regionally mandated plans to local contexts, which limits the ability of school principals to respond to local challenges (Mitchell, 2015;Yadete, 2012).…”
Section: Challenges In Local-level Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Community participation in SBM is now commonplace in SSA (Khan 2006;Daun and Mundy 2011). As such, the reforms described above are not so much Ethiopian as global education policies (Verger, Novelli and Altinyelken 2012), advanced by hegemonic Western policy actors such as USAID, DFID and the World Bank (Tabulawa 2003;Mitchell 2015;Zapp 2017). The World Bank has argued that parental involvement in decision-making processes encourages demand for a higher quality of education and ensures that schools reflect local priorities and values.…”
Section: Introductionmentioning
confidence: 99%
“…is study attempted to fill the gaps observed within the past studies that had utilized quantitative and regulating approaches. ird, for the past two decades, the Ethiopian higher education system has been developing rapidly, and in spite of this fast expansion, it created a slew of new problems, such as funding deficiencies and weakening of the quality of education [12].…”
Section: Introductionmentioning
confidence: 99%